Digital Interactive Media to Improve Children's Self-Protection from Sexual Abuse in Primary Schools - Firstca Rachma Apbrilia; Murfiah Dewi Wulandari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Cases of sexual abuse involving primary school children demonstrate the importance of teaching children to protect themselves from an early age using learning methods that are appropriate for their stage of development. Children's lack of understanding of personal boundaries and how to protect themselves makes them vulnerable to becoming victims. Education on self-protection needs to be delivered through approaches that are appropriate for children's characteristics, one of which is through interactive digital media. Interactive digital media is an engaging, communicative and easy-to-understand learning tool. Research shows that the use of interactive digital media can help children understand, recognise, and respond to ways of preventing sexual abuse. Children learn to recognise their own body parts, know the limits of interaction, and know what to do when they are in risky situations. In this study, digital interactive media can be used as an alternative to thematic learning in primary schools, especially in teaching self-protection values and character education in a fun and efficient way.